Diversity, stratification and temporal dynamics of geometrid moths (lepidoptera: geometridae) in Kubah Lowland Mixed Dipterocarp Forest, Sarawak - Irene, Christianus (Universiti Malaysia Sarawak (UNIMAS), 2012)
The diversity and stratification of the geometrid moths was investigated in a mixed dipterocarp forest, Kubah National Park, Sarawak. Modified Pennsylvanian light traps illuminated with a 160 Watt mercury vapour lamp were used to sample moths in the understorey (1 m) and canopy (32 m) strata. From a total of 336 samples, 916 individuals representing 173 species of geometrid moths were recorded. A total of 149 species and 675 individuals of geometrids were sampled in the understorey while 100 species and 241 individuals in the canopy stratu Overall, species diversity of geometrid moth in Kubah mixed dipterocarp forest was found to be considerably high (ex = 63.09 ±3 AI) for a single moth family and fell in the range of previously reported diversity score in Bornean rain forests. Results from the present study unequivocally showed that both understorey (ex = 59.17 ± 3.66) and canopy (ex = 64.09 ± 6.7) strata did not differ significantly in terms of diversity, however species richness and abundance tend to be numerica]Jy high in the understorey stratum. Kubah lowland mixed dipterocarp forest was characterised by the dominance of Ennominae and the presence of the least diverse Bomean geometrid subfamily Oenochrominae. A unimodal pattem with a peak of abundance in the understorey stratum was detected in Ennominae and ground specialists were represented from the tribes Hypochrosini, Boarmiini and Baptini. Markedly, data from the present study revealed that geometrid moth populations fluctuate through time, particularly the subfamily Ennominae and Geometrinae. Yet, the fluctuations in geometrid moth populations in response to meteorological factors and moonlight illumination were insignificant.